Factors affective to the competitiveness Hotel Business in Luang Prabang - SYOUDOMPHANH, Piet; YANGSANSAY, Chahue; VATTHANA, Mongkhoun (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
The purpose of this study was to study the business conditions of the entrepreneurs' hotels. to study the hotel operator’s competitiveness business and to study the affecting competitiveness factors of hotel operators in Prabang, Luang Prabang province. 355 participants who were the hotel operators in Luang Prabang province involved in this study. Questionnaires was used to measure hotel operators in this research. Data collection was analyzed by Stepwise method to satisfy the frequency, percentage, mean value, standard deviation and multiple regression equation. The finding of this study showed: 1) The mostly of 355 hotel operators were the individual ownership micro enterprise business only which their resort, hotel and quest house are 2-star service level. The business was run by their own funds according to the accumulated profit capital of the business as a large part. An important reason for starting the business is from the motivation of the location and the transportation route with a period of business at the hotel between 13 years and 15 years covering 46.76%, with an average monthly income of less than 50 million kip. The competitiveness of hotel business operators as a whole give’s importance to many levels, including the ability to respond quickly in providing services superior to business competitors, the ability to be a cost leader in providing services inferior to competitors, and the ability to create differences in services that are different from competitors. 3) Internal factors affecting the competitiveness of the hotel business in Prabang, Luang Prabang include 6 factors: physical factors, distribution channel factors, competitive strength factors, marketing promotion factors, product factors, and service process factors. In addition, the external environmental factors that affect the competitiveness of hotel business in Luang Prabang province include four factors: technological factors, economic factors, cultural-social factors, and political factors.